Pain intensity and depression level in chronic temporomandibular disorders patients - Raul Elton Araújo Borges; Luana da Rocha Alves Mendonça; Bruno César de Vasconcelos Gurgel; Angelo Giuseppe Roncalli; Patrícia dos Santos Calderon (Revista da Faculdade de Odontologia de Porto Alegre, 2021)
Aim: The aim of this study was to assess the correlation between pain intensity and the level of depression in patients with chronic temporomandibular disorders (TMD). Materials and methods: Fifty-five volunteers diagnosed by the Research Diagnostic Criteria (RDC/TMD) were assessed for pain intensity and level of depression. Pain intensity and level of depression were assessed using a visual analysis scale and Beck depression inventory, respectively. Data analysis was conducted using confidence intervals and Pearson’s chi-square test (p< 0.05). Results: The results demonstrated that non-depressed individuals (43.6%) showed a mean pain intensity of 28.27mm, those with mild depression (38.2%) 34.24mm, and those moderate depression (18.2%) 50.7mm. Statistical analysis showed that there was a positive and significant correlation between pain intensity and level of depression (p=0.004). Discussion: This study found a positive correlation between pain intensity and depression level in chronic TMD patients. However, it has not been elucidated yet how TMD are correlated to depression and in which way depression can influence its onset and perpetuation. Conclusion: The level of depression may play an important role in the intensity of chronic pain, therefore, a multidisciplinary intervention seems to be important for the treatment success.